Supervision of the Principal in Improving the Quality of Education - Faizah, Faizah; Lian, Bukman; Puspita, Yenny (Yayasan Sembilan Pemuda Indonesia, 2023)
This study aims to describe how school principal supervision at SMPT Al-Muhibbin Betung in Banyuasin Regency improved educational quality. This research strategy uses a qualitative, descriptive methodology. Teachers and school principals are sources of study data. Techniques for gathering data that include interviewing, observing, and documenting. Techniques for data analysis include data reduction, data display, and data verification/deduction. According to the study’s findings, SMPT Al-Muhibbiin Betung Betung Regency’s school principals’ oversight of efforts to raise academic standards is rated as good. The quality of education in schools is improved by the policies of the principals. It is believed that the infrastructure and amenities of schools do not adequately support children’ learning needs.